NARCISSISM PORTRAYED BY HATSUMOMO IN ARTHUR GOLDEN’S MEMOIRS OF A GEISHA - Dinda Titin Aprilia; Meni L isteti Hulu; Ismarini Hutabarat (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2022)
This research discussed Narcissism Portrayed by Hatsumomo in Arthur Golden’s Memoirs of a Geisha. The writer applied the theory of Narcissism Portrayed by Hatsumomo in Arthur Golden’s Memoirs of a Geisha as the unit analysis. The theory of Narcissism Portrayed by Hatsumomo in Arthur Golden’s Memoirs of a Geisha is used by the psycho-literature approach. The method of the research is descriptive qualitative. The reason for using this method is because this method is the most appropriate to be applied in this research. The author can find a comprehensive and deep description of narcissism in literary works. By using the qualitative method, the author can obtain the complete data and the data has high credibility. First, the research focuses on the narcissism portrayed by Hatsumomo in Arthur Golden’s Memoirs of a Geisha by analyzing the lines of her in the novel. By referring to the discussion, finally, the author comes to a conclusion that Hatsumomo has shown her narcissism that is reflected by her grandiosity sense and lack of empathy caused by her privilege in Okiya.